Landing on the spot: Approaches to outflow tract PVCs; from ECG to EGMs to intracardiac echocardiography. Issue 8 (20th June 2021) - Hadjis, Alexios; Frontera, Antonio; Limite, Luca Rosario; Lipartiti, Felicia; Tsitsinakis, George; Vlachos, Konstantinos; Becker, Giuliano; Sturmer, Marcio; Jaïs, Pierre; Hsia, Henry; Gerstenfeld, Edward; Della Bella, Paolo
Abstract: Premature ventricular complexes (PVCs) are increasingly recognized, as the use of ECG wearables becomes more widespread. In particular, PVCs arising from both the right ventricular outflow tract (RVOT) and left ventricular outflow tract (LVOT) comprise the majority of these arrhythmias and form a significant component of an electrophysiology practice. A keen understanding of the correlative anatomy of the outflow tracts, in addition to recognizing key ECG indices illustrating PVC sites of origin, are fundamental in preparing for a successful ablation. Patient selection, incorporating symptomatology, structural disease, and PVC burden can pose a challenge, though tools such as the ABC‐VT risk score may help identify those patients with a higher risk of clinical deterioration. Utilizing intracardiac echocardiography to highlight salient anatomic features not visible with fluoroscopy allows for a more precise and safer ablation. Interpretation of intracardiac EGMs, and the careful examination for low amplitude highly fractionated pre‐potentials, enhanced by the advent of new developed mapping/ablation catheters, remains crucial. Utilizing these tools will guide the electrophysiologist to an efficient and effective outflow tract PVC ablation.